Diagnosing and Changing Organizational Culture : based on the Com peting Values Framework - Cameron, Kim S., 1946-; Quinn, Robert E., 1946- (San Francisco, CA : Jossey-Bass, 2011)
"The Third Edition of this key resource provides a means of understa nding and changing organizational culture in order to make organization s more effective. It provides validated instruments for diagnosing orga nizational culture and management competency; a theoretical framework ( competing values) for understanding organizational culture; and a syste matic strategy and methodology for changing organizational culture and personal behavior. New edition includes online versions of the MSAI and OCAI assessments and new discussions of the implications of national c ultural profiles"--
Includes bibliographical references (p. 253-259) and index.
Includes bibliographical references and index.
Keywords: Organizational change; Corporate culture